Need for more TB vaccine field sites. - Mcshane, H (2009)
Efforts to control the tuberculosis (TB) epidemic have been challenged by both the geographical overlap with the HIV pandemic, and the emergence of multi - and extensively - drug-resistant strains of Mycobacterium tuberculosis. There is, therefore, an urgent global need for an improved vaccine. However, the development of an improved vaccine is scientifically and logistically challenging. Immunological correlates or biomarkers of protection are not known and there is no perfect preclinical animal model with which to predict success in humans. Indeed, vaccine development in general is time-consuming and costly. One of the many road-blocks to the development of new TB vaccines is the availability of field sites that are suitable for large scale Phase IIb/III efficacy testing. Because disease incidence is low, even though prevalence is high, Phase IIb efficacy trials involve several thousand subjects, and require lengthy follow-up. Phase III licensure trials will need to be even larger, and are likely to require the involvement of multiple field sites. There is currently inadequate capacity within high-burden TB countries to conduct these essential trials. We need to invest now to expand current capacity if we are to reduce the time taken to develop new vaccines.